Evaluative Language in Romanian and US Regional Newspapers - A Comparative Approach - Chefneux Gabriela (Bulletin of Transilvania University, 2020)
The paper analyses the way in which evaluative language in used in two regional newspapers – a US and a Romanian one. It starts from two articles that cover a similar topic, namely the mining disasters that took place in the two areas, and studies the way in which the disaster and the people responsible for it are presented. The analytical framework for the analysis is based on Martin and White’s definition of appraisal in terms of attitude, engagement and graduation and the analysis focuses on the similarities and differences between the two articles in terms of evaluation and its linguistic realizations.